Adding systematic biopsy to magnetic resonance ultrasound fusion targeted biopsy of the prostate in men with previous negative biopsy or enrolled in active surveillance programs: A prospective single center, randomized study. Issue 37 (11th September 2020) - Porreca, Angelo; Del Giudice, Francesco; Giampaoli, Marco; D'Agostino, Daniele; Romagnoli, Daniele; Corsi, Paolo; Del Rosso, Alessandro; Maggi, Martina; Chung, Benjamin I.; Ferro, Matteo; de Cobelli, Ottavio; Lucarelli, Giuseppe; et al.
Abstract : Abstract: Magnetic resonance imaging (MRI) targeted biopsy (TBx) of the prostate demonstrated to improve detection rate (DR) of clinically significant prostate cancer (csPCa) in biopsy-naive patients achieving strong level of evidence. Nevertheless, the csPCa yield for TBx alone versus TBx plus systematic biopsy (SBx) after accounting for overlapping of SBx cores with TBx cores, in prior-negative or active surveillance (AS) patients has not been well established. The objective of the study was to investigate benefits in terms of detection rate and pathological stratification of prostate cancer (PCa) using contextual SBx during MRI-TBx. Patients previously submitted to negative-SBx (cohort A) and those enrolled in an AS program (cohort B) who showed at least 1 suspicious area with a PIRADSv2 score ≥ 3 were prospectively and randomly assigned to only TBx strategy versus TBx plus SBx strategy. SBx locations could not encompass the TBx sites, so that the results of each type of biopsy were independent and did not overlap. A total of 312 patients were included in the 2 cohorts (cohort A: 213 cases; cohort B: 99 cases). No significant differences were found in terms of overall PCa-DR (77.6% vs 69.6% respectively; P  = .36) and csPCa-DR (48.2% vs 60.9 respectively; P  = .12). The MRI-TBx alone cohort showed higher csPCa/PCa ratio (87.5% vs 62.2%; P  = .03). The MRI-TBx plus SBx group subanalysis showed significantly higher csPCa-DR obtained at the MRI-TBx cores when compared with the SBx cores (43.7% vs 24.1%, respectively; P  = .01). Independently to age, prostatic-specific antigen and prostate imaging-reporting and data system score, either in rebiopsy (OR 0.43, 0.21–0.97) or AS (OR 0.46, 0.32–0.89) setting, SBx cores were negatively associated with the csPCa-DR when combined to TBx cores. MRI-TBx should be considered the elective method to perform prostate biopsy in patients with previous negative SBx and those considered for an AS program. Adding SBx samples to MRI-TBx did not improve detection rate of csPCa.